The Effectiveness of Endorser’s Credibility on Purchase Decisions (A Study of Instagram Account @kulinerbandung) - Dinda Farissa Faatin; Agus Sudono; Armandha Redo Pratama (Gastronomy Tourism Journal, 2022)
This study aims to analyze the effectiveness of endorser credibility on purchasing decisions. The research method implemented is descriptive and verification method with quantitative research and 100 respondents. In this study, the independent variable is the credibility of the endorser which consists of attractiveness, trustworthiness, and expertise. Meanwhile, for the dependent variable, namely is the purchase decision. The analytical techniques used are normality test, simple linear regression analysis, correlation analysis, coefficient of determination, and T test with testing using SPSS version 26 application and Microsoft Excel. The results of this research data processing resulted in a T count value of 14.320 T table 1.985 so it was concluded that there was an influence of endorser credibility on purchasing decisions with the object of research @kulinerbandung.